1999
DOI: 10.1074/jbc.274.28.19868
|View full text |Cite
|
Sign up to set email alerts
|

Topological Localization of the Carboxyl-Terminal Domain of RNA Polymerase II in the Initiation Complex

Abstract: The carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II (RNAP II) functions at multiple stages of transcription and is involved in the coupling of transcription to pre-mRNA processing. We have used site-specific protein-DNA photocross-linking to determine the position of the CTD along promoter DNA in the transcriptional pre-initiation complex. Comparison of the promoter contacts made by RNAP II with or without the CTD indicate that the CTD approaches promoter DNA downstream of the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Binding to TAR RNA could serve to position the P-TEFb complex adjacent to the RNA exit channel, which is implicated from structural studies to lie near the RNAPII CTD (10). We show here that Tat can promote phosphorylation of the CTD by CycT1-CDK9 through binding to the phosphorylated substrate via the arginine-rich motif and bridging of the P-TEFb complex to its substrate.…”
Section: Discussionmentioning
confidence: 82%
“…Binding to TAR RNA could serve to position the P-TEFb complex adjacent to the RNA exit channel, which is implicated from structural studies to lie near the RNAPII CTD (10). We show here that Tat can promote phosphorylation of the CTD by CycT1-CDK9 through binding to the phosphorylated substrate via the arginine-rich motif and bridging of the P-TEFb complex to its substrate.…”
Section: Discussionmentioning
confidence: 82%
“…6). Because the CTD and the RNA exit channel are closely juxtaposed in the initiation complex (39,40), transit through the CTD may facilitate their unloading to the nascent pre-mRNA. If not loaded rapidly after transcription, secondary structure formation on the pre-mRNA may compromise the recognition of splicing signals by splicing factors.…”
Section: Discussionmentioning
confidence: 99%
“…In preinitiation complexes the CTD is buried close to the DNA template and surrounded by basal transcription factors, including TFIIH, and proteins of the mediator complex. Cross-linking studies have shown that in preinitiation complexes the polymerase is orientated with CTD making contacts with the DNA template at around position 16, downstream of the transcription start site (15). The repeat unit of each heptapeptide in the CTD contains two SPXX motifs (SPTS and SPSY) that allow the CTD to fold into a compact beta-turn stabilized by a side chain-main chain interaction (5).…”
Section: Discussionmentioning
confidence: 99%